Poikiloderma With Neutropenia and Mastocytosis: A Case Report and a Review of Dermatological Signs - Piccolo, Vincenzo; Russo, Teresa; Di Pinto, Daniela; Pota, Elvira; Di Martino, Martina; Piluso, Giulio; Ronchi, Andrea; Argenziano, Giuseppe; Di Brizzi, Eugenia Veronica; Santoro, Claudia (Frontiers in Medicine, 2021)
Poikiloderma with neutropenia (PN) represents a very rare genetic disorder mainly characterized by poikiloderma and congenital neutropenia, which explains the recurrence of respiratory infections and risk to develop bronchiectasis. Patients are also prone to develop hematological and skin cancers. Herein we present a patient, the only one child of apparently unrelated Serbian parents, with PN due to a homozygous mutation NM_024598.3:c.243G>A (p.Trp81Ter) of USB1, who had an early onset of poikiloderma (1 year of age) associated to cutaneous mastocytosis. We also provide a review the literature about this uncommon condition with a focus on dermatological findings.